Green Sukuk Investment: Student's Role And Interest In Realizing A Golden Indonesia 2045 - Umi Masruro; Ubeid Fandi Nasrulloh (Universitas Brawijaya, 2022)
Abstract: Green Sukuk is an environmentally sound investment, this investment was first issued in November 2019 with serial number ST006. Furthermore, green Sukuk reopened in November 2020 with serial number ST007. Through the issuance of green Sukuk, the government can finance green projects to reduce climate change, such as reducing greenhouse gases. The research method used is a qualitative method. The purpose of this study is to determine the role of green Sukuk in realizing Indonesia gold in 2045. The subjects of this study are students who are less aware of the existence of green Sukuk and investors who have participated in green Sukuk. Through this research, it will be known the role of green Sukuk in realizing Indonesia gold in 2045. The results of this research are that not many people know about the presence of green Sukuk so it needs to be studied more deeply. Students who have no/little income cannot participate in green Sukuk investment. For that students need to plan capital for the next few years to invest. Thus, students as part of society are ready to contribute through green Sukuk to realize Golden Indonesia 2045 with all the potential that exists.Â